PENGARUH MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING (SFE) BERBANTUAN MEDIA CANVA TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SEKOLAH DASAR - Adesti Novita Sari; Erna Suwangsih; Primanita Sholihah Rosmana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study focuses on the low mathematical critical thinking skills of students, as they often struggle to modify mathematical models. The purpose of this study was to determine the effect and improvement of the Student Facilitator and Explaining (SFE) learning model assisted by canva media on the mathematical critical thinking skills of elementary school students. This research was conducted in a class IV elementary school, focusing on the mathematics subject of flat building materials. The class used class IVA as the experimental class using the SFE learning model assisted by canva media, while class IVC as the control class used the Group Investigation (GI) learning model. The research method used is a quasi-experiment with a non-equivalent control group design and the technique used in selecting samples is purposive sampling. The sample used amounted to 52 students with each class of 26 students. Based on the research results, the SFE learning model has an effect of 56% on students' mathematical critical thinking skills. Then, based on the results of the average N-Gain of the experimental class of 78.00, while in the control class of 62.38. Thus, it can be concluded that the use of the SFE learning model assisted by canva media can provide a better influence and improve students' mathematical critical thinking skills in class IV flat building material.